Antibiotic Resistance and Virulence Genes Detection among the Enterococcus faecalis Isolated from Swiftlet Industry in Borneo - Sui Sien LEONG; Samuel LIHAN; Hwa Chuan CHIA (Tehran University of Medical Sciences, 2020)
No Abstract